A Copyright Snapshot: the Impact of New Copyright Legislation on Information Professionals. (14th December 2015) - Stannard, Emily
Abstract: This article, written by Emily Stannard, is based on her presentation at the 2015 BIALL Annual Conference. The article discusses the recent statutory changes to the Copyright, Designs and Patents Act 1988 and reflects on the impact it has had on information professionals, especially those working within the cultural heritage and education sectors. The wording of the legislation is considered in detail with the aid of case law to provide context where necessary, particularly with reference to fair dealing provisions. Developments within the Digital Single Market of the European Union also have a significant impact on national copyright law, and it is imperative that information professionals remain informed about upcoming copyright initiatives as well as making sense of the new statutory instruments.